Senior High School Students’ Literacy Profile on Energy Conversion Process - Nugraha, Abdurrohman Khotim; Rochman, Chaerul; Nasrudin, Dindin (Universitas Negeri Malang, 2022)
One of the factors supporting the success of the energy transition program is community literacy. The purpose of this study is to provide an overview of the energy literacy profile of students in the energy conversion process. This study used a survey method by distributing energy literacy questionnaires to students of class XII MIPA at the State Senior High School in West Java, Indonesia. The results showed that the majority of student literacy was in a low category (41.9%). The percentage of students who answered correctly on the knowledge aspect of energy conversion was 62.6%, knowledge of physics concepts in energy conversion was 37.4%, knowledge of aspects of energy conversion benefits was 40.0%, and the best attitude related to hydropower by 50.3%. This study concludes that the students’ energy literacy level, primarily in energy conversion, is still in the low category. Therefore, energy education to improve students’ energy literacy is still very much needed.Keywords: energy conversion, energy literacy, energy education, renewable energy AbstrakSalah satu faktor pendukung keberhasilan program konversi energi adalah literasi masyarakat. Tujuan dari penelitian ini adalah untuk memberikan gambaran tentang profil literasi energi peserta didik dalam proses konversi energi. Penelitian ini menggunakan metode survei dengan menyebarkan instrumen literasi energi melalui angket kepada 31 siswa kelas XII MIPA SMA Negeri di Jawa Barat. Hasil penelitian menunjukkan bahwa sebagian besar literasi peserta didik menunjukkan kategori rendah (41,9%). Persentase siswa yang menjawab benar pada aspek pengetahuan konversi energi sebesar 62,6%, pengetahuan konsep fisika dalam konversi energi sebesar 37,4%, pengetahuan aspek manfaat konversi energi sebesar 40,0%, dan sikap terbaik terkait PLTA sebesar 50,3%. Penelitian ini menyimpulkan bahwa tingkat literasi energi peserta didik dalam konversi energi masih dalam kategori rendah. Oleh karena itu, pendidikan energi untuk meningkatkan literasi energi peserta didik masih sangat dibutuhkan.Kata Kunci: konversi energi, literasi energi, pendidikan energi, energi terbarukan